Agricultural Regionalization of Bangladesh Based on Productivity and Analysis of Spatial Dependencies of for Productivity Between the Districts of Bangladesh - Md Musfiqur Rahman Bhuiya; Hossain Mohiuddin (Journal of Bangladesh Institute of Planners, 2013)
Agricultural productivity of the Bangladesh are not equal all districts, some are in very in worse condition. This creates a dependency tendency for the low productive districts To identify the low productive districts for their agricultural development plan it is necessary to identify them through agricultural regionalization. The purpose of this study is to make agricultural regionalization of the 64 districts of the Bangladesh based on agricultural productivity and lists out probable hindrance causing low productivity. Productivity index was used as a parameter of agricultural productivity. Moran-I concept has been used to identify spatial dependencies between different regions. Scatter plot and Percentile value has been used to identify the outlier districts with extremely low and high productivity. The study has divided the whole country into four regions which will be helpful for taking policy for the agricultural development on basis their production level. From the analysis of degree of agricultural productivity dependencies between districts can be helpful for setting up agricultural development priority. The study also suggests possible initiatives for agricultural development on the basis of the study. Journal of Bangladesh Institute of Planners, Vol. 6, Dec 2013, pp. 181-189